The partial characterisation of the terpene synthase genes implicated in the defence response by Pinus patula and Pinus tecunumanii to Fusarium circinatum - Naidoo, Sanushka (University of Pretoria, 2020)
Mini Dissertation (MSc)--University of Pretoria, 2020.